Switching Assistance for Exoskeletons During Cyclic Motions - Tagliamonte, Nevio Luigi; Valentini, Simona; Sudano, Angelo; Portaccio, Iacopo; De Leonardis, Chiara; Formica, Domenico; Accoto, Dino (Frontiers in Neurorobotics, 2019)
This paper proposes a novel control algorithm for torque-controlled exoskeletons assisting cyclic movements. The control strategy is based on the injection of energy parcels into the human-robot system to preserve a stable limit cycle. The proposed controller was experimentally validated on 8 healthy subjects performing knee flexion-extension in unassisted and assisted conditions with a timing that minimizes perturbations, i.e. when the angular momentum is maximum. Electromyographic activity of main flexor-extensor knee muscles showed that the proposed controller mostly favors extensor muscles during extension, with a statistically significant reduction in muscular activity in the range of 10-20% in 60 out of 72 trials (i.e. 83%), while no effect related to swinging speed was recorded (speed variation was lower than 10% in 92% of the trials). In the remaining cases muscular activity increment, when statistically significant, was less than 10%. These results showed that the proposed algorithm reduced muscular effort during the most energetically demanding part of the movement (the extension of the knee against gravity) without perturbing the spatio-temporal characteristics of the task and making it particularly suitable for application in exoskeleton-assisted cyclic motions.